The ghost of Jim Crow how Southern moderates used Brown v. Board of Education to stall civil rights - Walker, Anders (Oxford University Press, 2009)
This title is an interpretation of the civil rights movement through the work of Southern moderates whose opposition to integration was far quieter than massive resisters with far-reaching effects.